2022
DOI: 10.3390/kidneydial2010006
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 mRNA Vaccine Immunogenicity in Hemodialysis Patients: Promising Vaccine Protection That May Be Hindered by Fluid Overload

Abstract: Background: Due to their immunocompromised conditions, hemodialysis (HD) patients are at high risk of being infected with SARS-CoV-2 with poor clinical outcomes. We explored safety, efficacy and variability factors associated with vaccine immune response in these patients. Methods: From 18 January to 30 April 2021, 87 HD patients were enrolled in this study and subdivided in two sub-groups: SARS-CoV-2 positive prior to vaccination and naïve patients. The vaccination protocol included two intramuscular shots of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Studies have shown that HD patients also have an impaired immune response to vaccines against hepatitis B [4], pneumococcal capsular polysaccharide vaccine [5], and influenza [6], with lower seroconversion rates and waning titres with time. The reduced efficacy of these vaccines in HD patients has been attributed to a variety of factors such as retention of uremic solutes, age, gender, body weight, nutritional status, seropositivity for antibodies against hepatitis C virus or human immunodeficiency virus, low serum albumin, possession of the major histocompatibility complex haplotypes, blood transfusion history, volume overload, and the acceleration of immunosenescence induced by chronic inflammation [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that HD patients also have an impaired immune response to vaccines against hepatitis B [4], pneumococcal capsular polysaccharide vaccine [5], and influenza [6], with lower seroconversion rates and waning titres with time. The reduced efficacy of these vaccines in HD patients has been attributed to a variety of factors such as retention of uremic solutes, age, gender, body weight, nutritional status, seropositivity for antibodies against hepatitis C virus or human immunodeficiency virus, low serum albumin, possession of the major histocompatibility complex haplotypes, blood transfusion history, volume overload, and the acceleration of immunosenescence induced by chronic inflammation [7][8][9].…”
Section: Introductionmentioning
confidence: 99%